2005
DOI: 10.1177/153537020523000905
|View full text |Cite
|
Sign up to set email alerts
|

The HIV-1 Tat Protein Selectively Enhances CXCR4 and Inhibits CCR5 Expression in Megakaryocytic K562 Cells

Abstract: The hematopoietic compartments act as long-term reservoirs for human immunodeficiency virus type-1 (HIV-1). Although hematopoietic progenitor cells (HPCs) are rarely infectable, HPCs committed to the megakaryocytic lineage can be infected and support a productive infection by both the X4 and R5 strains of HIV-1. Indeed, in contrast to the CD34+ progenitors, the lineage-committed HPCs express high levels of the HIV-1 co-receptors, CXCR4 and CCR5. The HIV-1 transactivator (Tat) protein has been shown to alter co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…The array included human chemokine receptor genes CCR1, CCR3, CCR5 and CXCR4. These receptors were not expressed in the K562 cells and there were no changes of expression in K562‐U51A cells consistent with previous reports on undifferentiated K562 cells 18. The chemokine genes included on the array were CXCR2 ligands CXCL8/IL8 or CXCL2/GROÎČ.…”
Section: Resultssupporting
confidence: 88%
“…The array included human chemokine receptor genes CCR1, CCR3, CCR5 and CXCR4. These receptors were not expressed in the K562 cells and there were no changes of expression in K562‐U51A cells consistent with previous reports on undifferentiated K562 cells 18. The chemokine genes included on the array were CXCR2 ligands CXCL8/IL8 or CXCL2/GROÎČ.…”
Section: Resultssupporting
confidence: 88%
“…Altogether, data from these findings indicate that the DENV-antigen–positive cells belong to the megakaryocytic lineage as defined by the coexpression of CD41 and CD61. It has been documented previously that megakaryocytic cells, in addition to the expression of CD61 and CD41, also express the chemokine receptor CCR5, which becomes downregulated during the course of human immunodeficiency virus infection [27]. Therefore, it is possible that CCR5, which is the receptor for the chemokines macrophage inflammatory protein-1a, macrophage inflammatory protein-1b, and RANTES, may be an important molecule contributing to or preventing DENV disease in response to infection.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports determined that the HIV-1 Tat protein alters co-receptor expression in lymphoid and myeloid cells [ 31 , 32 ]. Studies from our laboratory on the HPC cell line, K562 had also indicated that Tat can differentially regulate both CXCR4 and CCR5 expression in erythroid or megakaryocytic cells [ 33 ]. Although we have not measured Tat expression in the HD-HIV cells, the level of productive infection clearly suggests high levels of Tat protein which may be directly involved in changes in HIV-1 receptor expression observed in these cells.…”
Section: Discussionmentioning
confidence: 99%